Asymmetric Elimination Reaction on Chiral Metal Surfaces. Issue 2 (11th November 2021) - Stolz, Samuel; Danese, Martina; Di Giovannantonio, Marco; Urgel, José I.; Sun, Qiang; Kinikar, Amogh; Bommert, Max; Mishra, Shantanu; Brune, Harald; Gröning, Oliver; Passerone, Daniele; Widmer, Roland
Abstract: The production of enantiopure materials and molecules is of uttermost relevance in research and industry in numerous contexts, ranging from nonlinear optics to asymmetric synthesis. In the context of the latter, dehalogenation, which is an essential reaction step for a broad class of chemical reactions, is investigated; specifically, dehalogenation of prochiral 5‐bromo‐7‐methylbenz(a)anthracene (BMA) on prototypical, chiral, intermetallic PdGa111 surfaces under ultrahigh vacuum conditions. Asymmetric halogen elimination is demonstrated by combining temperature‐programmed X‐ray photoelectron spectroscopy, scanning probe microscopy, and density functional theory. On the PdGa111 surfaces, the difference in debromination temperatures for the two BMA surface enantiomers amounts up to an unprecedented 46 K. The significant dependence of the dehalogenation temperature of the BMA surface enantiomers on the atomic termination of the PdGa111 surfaces implies that the ensemble effect is pronounced in this reaction step. These findings evidence enantiospecific control and hence promote intrinsically chiral crystals for asymmetric on‐surface synthesis. Abstract : Chiral intermetallic compounds are promising candidates to promote heterogeneous asymmetric catalysis. Combining experimental and theoretical surface science methods, enantiospecific control is demonstrated for a halogen elimination reaction with a difference in the debromination temperatures of the two surface enantiomers of up to an unprecedented 46 K on the prototypical chiral intermetallic PdGa111 surfaces.